2009
DOI: 10.2174/157016209789973628
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Transfer of Antiretroviral Drugs and Newborn Birth Weight in HIV-Infected Pregnant Women

Abstract: Although it is well known that antiretroviral drugs (ARVs) across the placenta in different extents, few data are available concerning the impact of the transplacental passage of ARVs on newborn outcome. The aim of this study is to evaluate the transplacental diffusion of ARVs and the clinical assessment of the newborn. Mother and cord lopinavir, nelfinavir, atazanavir and nevirapine plasma levels were determined by high-performance liquid chromatography. Newborn gestational age, weight, and Apgar score were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
2
25
1
1
Order By: Relevance
“…The concordance between the results obtained with the ex vivo placental perfusion model and the cord-to-maternal plasma (C:M) ratios has already been shown for various antiretroviral agents of the nucleoside reverse transcriptase inhibitor and protease inhibitor classes. Indeed, the results obtained with the perfused cotyledon model and suggesting a relatively high and low placental transfer for nucleotide reverse transcriptase inhibitors and protease inhibitors, respectively, are in accordance with those obtained in vivo using matched maternal and umbilical cord blood samples collected at the time of delivery (21,25,27,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). Nevertheless, despite the in vivo/ex vivo concordance reported in the literature, our results should be confirmed in vivo with calculation of ratios in paired maternal and cord blood samples.…”
Section: Discussionsupporting
confidence: 90%
“…The concordance between the results obtained with the ex vivo placental perfusion model and the cord-to-maternal plasma (C:M) ratios has already been shown for various antiretroviral agents of the nucleoside reverse transcriptase inhibitor and protease inhibitor classes. Indeed, the results obtained with the perfused cotyledon model and suggesting a relatively high and low placental transfer for nucleotide reverse transcriptase inhibitors and protease inhibitors, respectively, are in accordance with those obtained in vivo using matched maternal and umbilical cord blood samples collected at the time of delivery (21,25,27,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). Nevertheless, despite the in vivo/ex vivo concordance reported in the literature, our results should be confirmed in vivo with calculation of ratios in paired maternal and cord blood samples.…”
Section: Discussionsupporting
confidence: 90%
“…However, this ratio is mostly dependent on delivery time, and maternal and fetal samples are rarely taken simultaneously. The values reported previously varied from Ͻ1% to 57% (8,(19)(20)(21)(22). In the present study, the estimated ratio was 11.6%, confirming that LPV placental transfer is low.…”
Section: Discussionsupporting
confidence: 79%
“…Placental transfer was estimated based on the exposure ratio between fetal and maternal LPV/r AUCs for 12 h. The placental transfer was estimated to be 11.6% (1.2% to 48.9%). This value is slightly lower than those suggested for the fetal-to-maternal concentration ratio at delivery (14 to 20%) (8,(19)(20)(21)(22)(23).…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…Previous studies have demonstrated placental transfer, with drug concentrations approaching 1 g/ml in maternal and cord blood ratios for certain nucleoside (or nucleotide) reverse transcriptase inhibitors (NRTIs) (15)(16)(17)32) with slightly lower ratios reported for non-NRTIs (18)(19)(20) and even lower ratios for the protease inhibitors (16,21). Studies analyzing placental transfer of TFV have reported variable results, with maternal and cord blood concentration ratios ranging from 0.82 to 6.0 (16,18).…”
Section: Discussionmentioning
confidence: 99%